2013
DOI: 10.2298/gensr1303799y
|View full text |Cite
|
Sign up to set email alerts
|

Biocomputational genome-wide analysis of micro RNA genetic variability in some vertebrates

Abstract: MicroRNAs (miRNAs) are small endogenously expressed single-stranded RNAs that regulate gene expression post transcriptionally and shape diverse cellular pathways. miRNAs regulate a wide range of biological processes through the recognition of complementary sequences between miRNAs and their target genes. The present investigation aimed at determining in-silico the genetic variability of miRNA genes in some livestock and non-livestock species. Effects of single nucleotide polymorphisms (SNPs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Only pig and buffalo had ω >1 signifying positive selection; while other species with ω<1 are under purifying selection. Yakubu et al (2013b), in their study on MHC reported that, positive selection favours new variants thereby increasing allelic polymorphism (Bergstronm and Gyllensten, 1995) which in turn favours the ability of antigen-presenting cells to bind a wide array of self and nonself-peptides, thus conferring higher resistance to infectious diseases (Hedrick and Kim, 2000). Mutation in pig and buffalo increases fitness (Kosakovsky Pond, 2011) and this is expected to reflect on performance.…”
Section: Resultsmentioning
confidence: 99%
“…Only pig and buffalo had ω >1 signifying positive selection; while other species with ω<1 are under purifying selection. Yakubu et al (2013b), in their study on MHC reported that, positive selection favours new variants thereby increasing allelic polymorphism (Bergstronm and Gyllensten, 1995) which in turn favours the ability of antigen-presenting cells to bind a wide array of self and nonself-peptides, thus conferring higher resistance to infectious diseases (Hedrick and Kim, 2000). Mutation in pig and buffalo increases fitness (Kosakovsky Pond, 2011) and this is expected to reflect on performance.…”
Section: Resultsmentioning
confidence: 99%